(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Sustainable development is the concept that prioritises current demands without compromising the capacity of future generations The term sustainable development found importance after Bruntland Commission where it was used in 1987 in its report, our common future. Then the term Governance implied the structure for distributing the rights and responsibilities among different parties in the corporation and includes the rules and procedures for making decisions in corporate sector. This paper examines the modern concept of governance and sustainability in the context of cement industry in India. It is an attempt to understand and appreciate the importance of sustainability in the field of the cement corporations of India. This paper defines the key sustainability parameters and then reviews the various cement corporations in accordance to these parameters. This paper measures the sustainability against factors like economical, social and environmental. The findings of this paper conclude that cement industry in India has taken a major step in sustainable growth and development. The cement companies contribute to society, environment, communities, management of natural resources and building public properties in order to contribute to the Indian economy.